An approach to creativity and idea management in São Bento do Sul companies (Revista Brasileira de Contabilidade e Gestão, 2019)
This article presents part of the results of a research applied by Univille's Ideando Project to companies participating in ENIT - Business, Innovation and Technology Fair and Meeting, held in 2018, in the municipality of São Bento do Sul - SC. The quantitative approach provided data from the perspective of creative environments, use of idea management tools, and insight into the relationship between idea management and innovation. As a result, it is emphasized that the organizational culture and its ideas generation and management practices seem to lack structure and that the culture of innovation is still a strategic factor to be better understood by companies in the region, thus requiring more in-depth and comprehensive research.
Keywords: Creativity; Idea Management; Innovation